(untitled) (Simbiótica. Revista Eletrônica, 2026)
The article analyzes the methodological transition of a national evaluation research of the National Socio-Educational Attendance System (SINASE) to the virtual environment, due to the COVID-19 pandemic. The study prioritized on-line focus groups with technical teams and members of the Justice System. The advantages of the strategy are discussed, such as breaking down geographical barriers and the exchange of inter-institutional experiences, as well as technical challenges and limitations in body language and participant privacy. The analysis reveals that while technology enabled the continuity of the research, it also highlighted infrastructure inequalities and new power dynamics within the Rights Guarantee System. It concludes that the digital experience offered a critical prism on institutional integration, pointing towards more organic and less fragmented articulation in Brazilian socio-educational care.